Morfología floral, posición filogenética y delimitación taxonómica de Sarmenticola calceolaris (Oncidiinae: Orchidaceae) en el Río Momón, Iquitos, Perú - Vilcatoma Rodriguez, Eduardo Luis (2025)
The present study was conducted in a blackwater floodplain forest located on the left bank of the Momón River, 25.4 km from the city of Iquitos, with the objective of describing the floral morphology, determining the phylogenetic position, and taxonomically delimiting Sarmenticola calceolaris (Garay) Senghas & Garay, a small orchid rediscovered after 87 years of mystery. Morphological data were analyzed using RStudio software. New ITS and matK sequences were generated, complemented with data from GenBank, and subsequently processed with SuperCRUNCH pipeline. Phylogenetic inference by Maximum Likelihood (ML) was carried out using IQ-TREE software with 1000 Bootstrap replicates, and the best evolutionary model was selected with Model Finder Plus. The results indicated that Sarmenticola calceolaris exhibits distinctive morphological characteristics in its labellum, column, and pollinarium; however, discrepancies were observed with previous floral morphological descriptions. Additionally, phylogenetic analyses positioned Sarmenticola calceolaris as a sister taxon to Seegeriella pinifolia, with a Bootstrap support value of 80%. In conclusion, Sarmenticola calceolaris is delimited as an independent evolutionary lineage within the subtribe Oncidiinae, both morphologically and molecularly.